2014
DOI: 10.11144/javeriana.upsy13-1.adup
|View full text |Cite
|
Sign up to set email alerts
|

Dimensión afectiva de profesores universitarios acerca de su enseñanza: una exploración a través de la técnica de diferencial semántico

Abstract: A B s t r A C tThe main objective of this study is to increase our knowledge regarding professors' emotions about their teaching, as a component of teacher identity. In the first part, we present a comprehensive review of the literature about the types of teachers' emotions and teaching. In the second part we present the results of a validity study with a semantic differential scale developed to explore the emotions of university professors about their teaching. This scale was fulfilled by a sample of 198 univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 56 publications
0
4
0
4
Order By: Relevance
“…Por esta razón, se pone de manifiesto, tal y como señalan Serrano y Pontes (2016), que es indispensable en los programas de formación de maestros asumir de manera explícita la IPD. Igualmente, queda en evidencia que estos programas deben propiciar el desarrollo de habilidades en el profesorado para regular y utilizar sus emociones en los procesos de enseñanza, aprendizaje e interacción social (Hargreaves, 2000;Herrera & Buitrago, 2014;Sutton, 2004;Sutton & Wheatley, 2003), aportando a la motivación y autoevaluación del maestro, y la efectividad en la enseñanza (Badia et al, 2013). En concordancia con el estudio de Hascher & Hagenauer (2016), el nerviosismo, la ansiedad y la preocupación son emociones constantemente observables en la práctica de los docentes en formación, aspectos que deben ser abordados desde el currículo.…”
Section: Discussionunclassified
“…Por esta razón, se pone de manifiesto, tal y como señalan Serrano y Pontes (2016), que es indispensable en los programas de formación de maestros asumir de manera explícita la IPD. Igualmente, queda en evidencia que estos programas deben propiciar el desarrollo de habilidades en el profesorado para regular y utilizar sus emociones en los procesos de enseñanza, aprendizaje e interacción social (Hargreaves, 2000;Herrera & Buitrago, 2014;Sutton, 2004;Sutton & Wheatley, 2003), aportando a la motivación y autoevaluación del maestro, y la efectividad en la enseñanza (Badia et al, 2013). En concordancia con el estudio de Hascher & Hagenauer (2016), el nerviosismo, la ansiedad y la preocupación son emociones constantemente observables en la práctica de los docentes en formación, aspectos que deben ser abordados desde el currículo.…”
Section: Discussionunclassified
“…En el Factor organizacional se identificaron: la carga de trabajo del curso (Mardikyan y Badur, 2011), y las acciones de todos los involucrados en el proceso educativo (Carrasco et al, 2016). Finalmente, en el Factor personal destacaron: la motivación hacia la docencia (Badia-Garganté, 2013;Nsibande, 2020); y las creencias de los profesores acerca de la práctica de enseñanza (Bacci et al, 2019;Barrón-Tirado, 2015;Carrasco et al, 2016); entre otros. Fuente: Elaboración propia.…”
Section: Figura 5 Distribución De Las Características De Enseñanza Ef...unclassified
“…Although research has shown that teaching approaches are significant for teaching behavior and student learning, little is known about the link between HE teachers' emotions and teaching approaches or between HE teachers' emotions and emotion regulation (Kordts-Freudinger, 2017). The few available studies have consistently found a positive correlation between HE teachers' positive emotions or affect and a student-centered approach to teaching, which also includes the establishment of a positive climate in the classroom (Postareff and Lindblom-Ylanne, 2011;Trigwell, 2012;Badia Gargante et al, 2014;Meanwell and Kleiner, 2014;Kordts-Freudinger, 2017;Kordts-Freudinger and Thies, 2018).…”
Section: Attitudinal Changesmentioning
confidence: 99%